2020
DOI: 10.3389/fmicb.2020.569118
|View full text |Cite
|
Sign up to set email alerts
|

Systematically Studying the Optimal Amino Acid Distribution Patterns of the Amphiphilic Structure by Using the Ultrashort Amphiphiles

Abstract: Amphipathicity has traditionally been considered to be essential for the de novo design or systematic optimization of antimicrobial peptides (AMPs). However, the current research methods to study the relationship between amphiphilicity and antimicrobial activity are inappropriate, because the key parameters (hydrophobicity, positive charge, etc.) and secondary structure of AMPs are changed. To systematically and accurately study the effects of amphiphilicity on antimicrobial properties of AMPs, we designed par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 64 publications
0
22
0
Order By: Relevance
“…The secondary structure of peptides in PBS as well as in the membrane mimetic environments (30 mM SDS micelles in PBS and 50% TFE in PBS) was determined by CD spectroscopy. The CD spectra analyses were interpreted in accordance with published data 35 , 36 . As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The secondary structure of peptides in PBS as well as in the membrane mimetic environments (30 mM SDS micelles in PBS and 50% TFE in PBS) was determined by CD spectroscopy. The CD spectra analyses were interpreted in accordance with published data 35 , 36 . As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…At11 and At12 were obtained by introducing two hydrophobic amino acids in the hydrophilic region to make imperfect amphiphilicity. 51…”
Section: Resultsmentioning
confidence: 99%
“…At11 and At12 were obtained by introducing two hydrophobic amino acids in the hydrophilic region to make imperfect amphiphilicity. 51 Table 1 lists the twelve peptide sequences and their fundamental properties. All peptides contain an overall positive charge but different numbers of net charges and different hydrophobicities as determined by their retention times in RP-HPLC.…”
Section: Peptide Design and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…More importantly, Spohn et al found that resistance levels induced by AMP controls were significantly lower than the resistance levels evoked by antibiotic controls (Spohn et al, 2019). These advantages further indicated the potential of AMPs as substitution of antibiotics (Yang et al, 2019;He et al, 2020). Mechanistically, the stereotypical mechanism of AMP action includes the following three steps, largely preventing the occurrence of bacterial resistance: First, the cationic of AMPs exerts a binding process with the negatively charged surfaces of Gram-negative (outer membrane) or Gram-positive (cell wall) bacteria (Figures 1A,B).…”
Section: Introductionmentioning
confidence: 99%